Preliminary bacteriological examination of healthy and brown muscle syndrome-infected P. monodon. - Ubano, Theresa Buenafe (1994.)
The occurence of diseases in prawns are mostly attributed to bacterial infections. This study focuses on the determination of the total heterotrophic and total Vibrio load of the diseased P. monodon infected with Brown Muscle Syndrome (BMS) healthy and rearing water., The results indicated that a significantly greater (P<-0.01) heterotrophic and Vibrio count was detected in the muscle tissues of diseases prawns. This suggests that bacteria play an important role in the ensuance of BMS and this may have a public health implication. However, Vibrio spp. which are known to be the primary causative agent of many prawn diseases is detected to be significantly low (p<-0.01) compared to the total heterotrophic count. The rearing water, on the other hand, harbors a significantly greater (P<-0.01) number of heterotrophic bacteria compared to the Vibrio population. Vibrio spp. was also consistently detected in both the diseased and healthy prawn tissue and in the rearing water.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: P. Monodon -- Brown Muscle Syndrome